(untitled) (KULT_online, 2014)
By and large, in his new and highly recommended book sociologist Dirk Baecker presents a theory of culture following Luhmann’s claim that culture basically is a form of reflection upon social phenomena and their contingency. But how, one may ask, does society accomplish being its own spectator and not interrupt the reproduction of itself? Luhmann’s answer was that culture is a historicizing perspective unfolding this paradox in time dimension. Instead, Baecker emphasizes ambiguity of expectations and ambivalent connotations of symbols as a means by which agents in modern pluralistic society are regulating the limits of their own (systems, media, organizations, etc.).